2003
DOI: 10.1093/oxfordjournals.schbul.a006988
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic Twins Exhibit Numerous Epigenetic Differences: Clues to Twin Discordance?

Abstract: The goal of this pilot study was to explore the putative molecular mechanisms underlying the phenotypic discordance of monozygotic (MZ) twins. Thus, patterns of epigenetic DNA modification were investigated in the 5'-regulatory region of the dopamine D2 receptor gene (DRD2) in two pairs of monozygotic twins, one concordant and one discordant for schizophrenia. The bisulfite DNA modification-based approach was used to fine-map methylated cytosines in DRD2 in genomic DNA extracted from lymphocytes. Numerous DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
170
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(181 citation statements)
references
References 39 publications
6
170
0
5
Order By: Relevance
“…For example, environmental events (for example, early childhood stressors) correlate with the development of psychiatric disorders in adults (Heim and Nemeroff, 2001). Indeed, as witnessed by multiple studies of discordant monozygotic twins where one has the disorder and the other does not, epigenetic mechanisms must be operative to control behavior in genetically identical populations (Petronis et al, 2003). A critical question involves the mechanism by which early life events regulate long-term changes in behavior and sustained differences in gene expression.…”
Section: Increased Stress Sensitivity (Gender Specific)mentioning
confidence: 99%
“…For example, environmental events (for example, early childhood stressors) correlate with the development of psychiatric disorders in adults (Heim and Nemeroff, 2001). Indeed, as witnessed by multiple studies of discordant monozygotic twins where one has the disorder and the other does not, epigenetic mechanisms must be operative to control behavior in genetically identical populations (Petronis et al, 2003). A critical question involves the mechanism by which early life events regulate long-term changes in behavior and sustained differences in gene expression.…”
Section: Increased Stress Sensitivity (Gender Specific)mentioning
confidence: 99%
“…They analyzed the DNA samples obtained from two pairs of twins discordant or concordant for schizophrenia and examined the DNA methylation status of the upstream region of the dopamine D2 receptor. 9 They examined the difference of the DNA methylation status between twins, which was named 'epigenetic distance'. They reported that epigenetic difference was larger between discordant twins compared with concordant twins.…”
Section: Search For Epigenetic Discordance Between Mz Twinsmentioning
confidence: 99%
“…[6][7][8][9][10] These studies seem to have induced a paradigm shift to the third-generation twin research, from focusing on the higher concordance rate in MZ twins, to looking for the genetic or epigenetic difference between MZ discordant twins. 11 In this review, the theoretical concept of such study to search for genetic or epigenetic difference between MZ discordant twins is explained and its application to schizophrenia and bipolar disorder is summarized.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic factors are a more commonly detected source of variation between MZ twins and are an attractive mechanism for the observed phenotypic differences. 15,16 The role of epigenetic regulation of gene expression in complex diseases, including psychiatric disorders is attracting increasing molecular and epidemiological support. 17 The use of twins also increases capacity over population-based studies to conduct multivariate analyses to decipher complex relationships between genes and pleiotropic effects.…”
Section: Introductionmentioning
confidence: 99%